The mediating effect of religiosity on the relationship between attitude and adoption of cleanliness among IIUM students - Mohammed Bawazir, Ala Omar; Wok, Saodah; Jamalludin, Nur Hafifah (Kolej Universiti Islam Melaka, 2019)
Cleanliness is an essential element in Islam as it is a part of faith. As such, it is compulsory for Muslims to take care of their physical and spiritual cleanliness. To adopt cleanliness values, they need to understand the importance of the underlying principles of cleanliness in Islam. Guided by social learning theory (SLT), this study investigates the mediating effect of religiosity on the relationship between external and spiritual attitudes and the adoption of cleanliness among IIUM students. SLT helps to highlight the advantages of practicing external and spiritual cleanliness. This study employs a quantitative research design through the use of a questionnaire as an instrument for its survey involving 390 students from various Kulliyyah. This study found that the adoption of cleanliness values has a positive relationship with cleanliness. Also, religiosity partially mediates the relationship between attitude towards external cleanliness, attitude towards spiritual cleanliness, and the adoption of cleanliness values. Thus, this study sheds some light on the benefits of having a strong will in practicing cleanliness (externally and spiritually) in their daily routine and also helps in the adoption and development of a positive value which reflects one as a good Muslim. Therefore, the SLT holds true for the adoption of cleanliness.